Korelasi Tekanan Nadi sebagai Parameter Kekakuan Arteri dan Obesitas Sentral pada Mahasiswa Pria - Azkiya; Khairun Nisa Berawi; Ratri Mauluti Larasati; Susianti (BAPIN-ISMKI (Badan Analisis Pengembangan Ilmiah Nasional - Ikatan Senat Mahasiswa Kedokteran Indonesia), 2025)
Background: Central obesity is frequently linked to elevated blood pressure, however, not all individuals with this condition develop hypertension. Pulse pressure has been recognized as a more sensitive marker than conventional blood pressure in predicting cardiovascular risk. Consequently, monitoring pulse pressure in individuals with central obesity may serve as an important strategy for early identification of subclinical cardiovascular dysfunction. Method: This study employed an observational, cross-sectional design involving university students aged 18-21 years. Central obesity was assessed using waist circumference measurements based on WHO Asia-Pasific criteria. Pulse pressure was calculated as the difference between systolic and diastolic blood pressure, measured with a manual sphygmomanometer. The association between central obesity and pulse pressure was analyzed bivariately using the Chi-Square test. Results: Statistical analysis revealed no significant association between central obesity and pulse pressure (p > 0.05). Nevertheless, descriptive findings showed that the mean pulse pressure among individuals with central obesity (38.89 mmHg) tended to be lower than that of those without central obesity (40.77 mmHg). Discussion: This study demonstrated no significant relationship between central obesity and pulse pressure among male college students aged 18-21 years, although the centrally obese group exhibited a lower mean pulse pressure. The discrepancy from previous research may be attributed to the relatively young age of the respondents and the high number of individuals presenting with elevated blood pressure. Conclusion: This study found no significant association between central obesity and pulse pressure in male college students aged 18-21 years. However, a trend toward lower pulse pressure among centrally obese individuals was observed, potentially influenced by increased blood pressure. These findings suggest that pulse pressure continues to old potential an an early indicator of subclinical cardiovascular alterations.